Ultra-high vacuum cleaver for the preparation of ionic crystal surfaces - Sander, Tim; LIU, YI; Pham, Tuan; Ammon, Maximilian Michael; Devarajulu, Mirunalini; Maier, Sabine (Review of Scientific Instruments, 2022)
Cleaving single crystals in situ under ultra-high vacuum conditions provides a reliable and straightforward approach to prepare clean and atomically well-defined surfaces. Here, we present a versatile sample cleaver to efficiently prepare ionic crystal surfaces under ultra-high vacuum conditions, which is suitable for preparation of softer materials, such as alkali halides, and harder materials, such as metal oxides. One of the advantages of the presented cleaver design is that the cleaving blade and anvil to support the crystal are incorporated into the device. Therefore, no particularly strong mechanical manipulator is needed, and it is compatible with existing vacuum chambers equipped with an xyz-manipulator. We demonstrate atomically flat terraces and the atomic structure of NaCl(001), KBr(001), NiO(001), and MgO(001) cleavage planes prepared in situ under ultra-high vacuum conditions and imaged by low-temperature non-contact atomic force microscopy.& nbsp;Published under an exclusive license by AIP Publishing
CRIS-Team WoS Importer:2022-06-03